Mitigation of biofouling in agricultural water distribution systems with nanobubbles. (August 2020) - Xiao, Yang; Jiang, Sunny C.; Wang, Xiaoyao; Muhammad, Tahir; Song, Peng; Zhou, Bo; Zhou, Yunpeng; Li, Yunkai
Graphical abstract: Highlights: Nanobubbles (NBs) effectively controlled biofouling in irrigation pipelines. NBs shifted the bacterial communities and reduced their diversities in biofilm. NBs drastically decreased the deposition of mineral precipitation in biofilm. NBs treatment could provide an eco-friendly solution for biofouling control. Abstract: Biofouling poses considerable technical challenges to agricultural irrigation systems. Controlling biofouling with strong chemical biocides is not only expensive and sometimes ineffective, but also contributes to environmental pollution. This study investigated the application of nanobubbles (NBs) on minimizing biofouling in agricultural irrigation water pipelines. Treatment performances were assessed using low concentration bubbles (LCB) and high concentration bubbles (HCB) together with a negative control (CK: no-NBs). 16 s rRNA gene sequencing and X-ray diffraction were used to characterize the microbial community and mineral compositions of biofilms in water emitters. Results demonstrated that NBs effectively mitigated biofouling through reducing fixed-biomass by 31.3−52.1%. A significantly different microbial composition was found in the biofilm community with reduced biodiversity. Molecular ecological network analysis revealed that NBs were detrimental to the mutualistic interactions among microbial species – destabilizing the network complexity and size, which was expressed as decreasing in extracellular polymers and biofilm biomass. Furthermore, NBs significantly decreased the deposition of carbonate, silicate, phosphate, and quartz on the pipe surfaces, leading to reductions of total content of minerals in biofilms. Therefore, this study demonstrated that NBs treatment could be an effective, and eco-friendly solution for biofouling control in agricultural water distribution systems.